Bacteriophage-based decontamination to control environmental colonization by Staphylococcus capitis in neonatal intensive care units: An in vitro proof-of-concept - Chavignon, Marie; Kolenda, Camille; Medina, Mathieu; Bonhomme, Mélanie; Blazere, Leslie; Legendre, Tiphaine; Tristan, Anne; Laurent, Frédéric; Butin, Marine (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction In neonatal intensive care units (NICUs), the standard chemical-based disinfection procedures do not allow a complete eradication of pathogens from environmental surfaces. In particular, the clone Staphylococcus capitis NRCS-A, a significant pathogen in neonates, was shown to colonize neonatal incubators. The aim of this study was to evaluate the in vitro effect of a bacteriophage cocktail on NRCS-A eradication. Methods Three bacteriophages were isolated, genetically characterized and assessed for their host range using a collection of representative clinical strains (n=31) belonging to the clone NRCS-A. The efficacy of a cocktail including these three bacteriophages to eradicate the reference strain S. capitis NRCS-A CR01 was determined in comparison or in combination with the chemical disinfectant Surfanios Premium on either dry inoculum or biofilm-embedded bacteria. The emergence of bacterial resistance against the bacteriophages alone or in cocktail was evaluated by growth kinetics. Results The three bacteriophages belonged to two families and genera, namely Herelleviridae/Kayvirus for V1SC01 and V1SC04 and Rountreeviridae/Andhravirus for V1SC05. They were active against 17, 25 and 16 of the 31 tested strains respectively. Bacteriophage cocktails decreased the bacterial inoculum of both dry spots and biofilms, with a dose dependent effect. The sequential treatment with bacteriophages then Surfanios Premium did not show enhanced efficacy. No bacterial resistance was observed when using the bacteriophage cocktail. Discussion This study established a proof-of-concept for the use of bacteriophages to fight against S. capitis NRCS-A. Further investigations are needed using a larger bacterial collection and in real-life conditions before being able to use such technology in NICUs